We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
71
1
avatar+404 

If t(x) = 3-g(x) and g(x) = √x, then what is t(g(16))?

 May 16, 2019
 #1
avatar+8209 
+2

Let's find  g(16) .

 

g(x)  =  √x

                           Plug in  16  for  x .

g(16)  =  √16

 

g(16)  4

 

Now let's find t(4) .

 

t(x)  =  3 - g(x)

                           Plug in  4  for  x .

t(4)  =  3 - g(4)

                           And  g(4)  =  √4  =  2   so we can substitute  2  in for  g(4)

t(4)  =  3 - 2

 

t(4)  =  1

 

So.....

 

t( g(16) )  =  t( 4 )  =  1

 May 16, 2019

14 Online Users

avatar
avatar
avatar